Developing A Podcast Production Guidebook for Communication and Islamic Broadcasting Students - Robi’ah Machtumah Malayati; Ainun Fitri Mughiroh; Anwari; Moh. Slamet; Ahmad Fakhruddin Fajrul Islam; Bambang Sujatmiko; Advan Navis Zubaidi (Mediakita, 2025)
Podcasting, both audio and video (vodcast), is an effective tool to enhance students' skills in the field of communication. The Communication and Islamic Broadcasting Study Program (KPI) at Hasyim Asy'ari University (Unhasy) Tebuireng, Jombang, integrates podcast production into its curriculum to prepare students for the challenges of the Industry 4.0 and Society 5.0 era. Although the students have produced over 100 podcasts, the quality is still suboptimal, particularly in communication, sound stability, visual quality, and audience engagement. This research aims to develop a podcast production guidebook using the ADDIE model for KPI students at Unhasy. The results demonstrated that the instructional guidebook received validation from subject matter experts with a commendable score of 93% and from media experts with a score of 92%. Furthermore, when it was tested on the students, the guidebook yielded a feasibility rating of 82%. Those results indicate that the guidebook is highly feasible, signifying a high level of practicality and applicability. Although some aspects need improvement, such as adding practical materials, simplifying technical instructions, and focusing on the creative aspects of podcasting, this guidebook has helped improve podcast production quality and served as a key learning reference.